Goal Attainment Scaling Rehabilitation Improves Satisfaction with Work Activities for Younger Working Patients After Knee Arthroplasty: Results from the Randomized Controlled ACTION Trial. (19th August 2020) - Hoorntje, Alexander; Waterval-Witjes, Suzanne; Koenraadt, Koen L.M.; Kuijer, P. Paul F.M.; Blankevoort, Leendert; Kerkhoffs, Gino M.M.J.; van Geenen, Rutger C.I.
Abstract : Background: Knee arthroplasty (KA) is increasingly performed in relatively young, active patients. This heterogeneous patient population often has high expectations, including work resumption and performance of knee-demanding leisure-time activities. Goal attainment scaling (GAS) may personalize rehabilitation by using patient-specific, activity-oriented rehabilitation goals. Since unmet expectations are a leading cause of dissatisfaction after KA, personalized rehabilitation may improve patient satisfaction. We hypothesized that, compared with standard rehabilitation, GAS-based rehabilitation would result in younger, active patients having higher satisfaction regarding activities after KA. Methods: We performed a single-center randomized controlled trial. Eligible patients were <65 years of age, working outside the home, and scheduled to undergo unicompartmental or total KA. The required sample size was 120 patients. Using GAS, patients developed personal activity goals with a physiotherapist preoperatively. These goals were used to monitor patients' goal attainment and provide goal-specific feedback during postoperative outpatient rehabilitation. Standard rehabilitation consisted of regular outpatient physiotherapy visits. The primary outcome measures were visual analogue scale (VAS) scores (scale of 0 to 100) for satisfaction regarding activities of daily living and work and leisure-time activities 1 year postoperatively, which were analyzed using generalized estimating equation models. Results: Patient satisfaction with work activities was significantly higher in the GAS group (β = 10.7 points, 98% confidence interval [CI] = 2.0 to 19.4 points) than in the control group. Patient satisfaction with activities of daily living and leisure-time activities did not differ between groups. We found no differences in VAS satisfaction scores between unicompartmental KA and total KA. Conclusions: Personalized, goal-specific rehabilitation using GAS resulted in higher patient satisfaction with work activities, compared with standard rehabilitation, 1 year after KA. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.